La firma y sus decisiones óptimas en el tiempo: inventarios y capital fijo - Martirena Mantel, Ana María (1968)
The paper tries to extend the traditional analysis of the firm by studying its optimal dynamic behavior when facing the alternatives to invest in two types of stocks, inventories and fixes capital. The objective of the firm in this analysis was the search of the optimal way of satisfying a given pattern of demand which changes over time within the finite planning horizon. When the production function has fixed technological coefficients and net investment can be negative (by selling any excess equipment in a perfect second hand market) the conclusion was that the transactions motive for holding inventories disappears; both stocks turned out to be substitutes. In the more relevant case in which investment in fixed capital has a lower limit determined by depreciation, the conclusion about substitution is maintained most of the time. Only in special cases, depending on the course of demand over time and on prices, a relation of complementary will exist.